PREDICTION OF EXCHANGE RATE INTEGRATION IN FOUR EMERGING MARKET COUNTRIES - Ade Novalina; Rusiadi Rusiadi; Bhaktiar Efendi; Dilla Fadila Rusmawadi; Nasib Nasib (Jurnal Ekonomi, 2023)
This study analyzes monetary policy variables on exchange rate stability. Where is the purpose of this study to see the contribution of variable inflation, the amount of money in circulation, interest rates, and foreign exchange reserves in dealing with exchange rates? The problem that has existed so far is the inaccuracy of the policies used to maintain exchange rate stability. However, this study predicts being able to use monetary policy in dealing with exchange rate problems. Four countries will be studied, namely Indonesia, Malaysia, Thailand, and the Philippines. Analysis to see leading indicators per country using the ARDL Panel method. The results of interest rates and the money supply can become the main leading indicators (Indonesia, Malaysia, Thailand, and the Philippines), but their positions are unstable in the short run and long run. The main leading indicator of the effectiveness of monetary policy which can become the leading indicator for Indonesia, Malaysia, Thailand, and the Philippines in maintaining exchange rate stability is the interest rate variable seen from a short-run and long-run stability. Where the interest rate variable in the short term and long term is significant for the stability of the exchange rate.